Promising therapeutics of enterovirus 71 infection: sunshine behind cloud - You, Sheng-Yu; Chen, Shun-Hua; Wang, Shih-Min (Frontiers in Pharmacology, 2025)
Enterovirus 71 (EV71) infection gave a hard hit on young children because of fatal complication, brainstem encephalitis with pulmonary edema. The occurrence of severe EV71 infections highlight the urgent need for the development and repurposing of novel antivirals for medical use. Drugs target specific steps in the cycle of viral replication, and the modification of existing factors in EV71 immunopathogenesis deciphers the current approaches for developing antivirals. In addition to identifying chemical compounds, we highlight active constituents and explore underlying mechanisms of action of antimicrobial peptides and natural products that may be active against EV71 and provide pharmacological benefits.